1989
DOI: 10.1042/bj2620313
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of very-low-density-lipoprotein lipid secretion in hepatocyte cultures derived from diabetic animals

Abstract: Hepatocytes were derived from 2-3-day streptozotocin-diabetic rats and maintained in culture for up to 3 days. Compared with similar cultures from normal animals, these hepatocytes secreted less very-low-density-lipoprotein (VLDL) triacylglycerol, but the decrease in the secretion of VLDL non-esterified and esterified cholesterol was not so pronounced. This resulted in the secretion of relatively cholesterol-rich VLDL particles by the diabetic hepatocytes. Addition of insulin for a relatively short period (24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 60 publications
(73 reference statements)
4
34
0
1
Order By: Relevance
“…Studies in experimental models of diabetes demonstrate that insulin deficiency lowers hepatic apo B (28, 29) and VLDL-triglyceride secretion (40,41), and with long-term insulin treatment in vivo, hepatic apo B production normalizes (28). Our studies suggest a positive correlation between plasma insulin levels and hepatic triglyceride-rich lipoprotein production, and such a correlation is supported by studies which raise ambient plasma levels by insulin injection (72), continuous insulin infusion (73), and sucrosefeeding (74).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Studies in experimental models of diabetes demonstrate that insulin deficiency lowers hepatic apo B (28, 29) and VLDL-triglyceride secretion (40,41), and with long-term insulin treatment in vivo, hepatic apo B production normalizes (28). Our studies suggest a positive correlation between plasma insulin levels and hepatic triglyceride-rich lipoprotein production, and such a correlation is supported by studies which raise ambient plasma levels by insulin injection (72), continuous insulin infusion (73), and sucrosefeeding (74).…”
Section: Discussionsupporting
confidence: 71%
“…VLDL composition is altered in streptozotocin-induced diabetes with a marked reduction in apo E content (29,31,36) which may be a contributory factor to the catabolic defect, as apo E is an important ligand for hepatic lipoprotein receptors (37). Hepatic secretion of VLDL lipid (36,(38)(39)(40)(41) and apo B and E is substantially reduced in both primary cultures of hepatocytes (28,29) and perfused livers derived from diabetic rats (28,36). These findings suggest that the hyperlipidemia of experimental diabetes is primarily a result of the accumulation of intestinally derived chylomicrons and VLDL, and suggest further that the contribution of apo B-containing lipoproteins to the plasma by the liver in the hypoinsulinemic diabetic state is relatively small.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Physiological concentrations of insulin have been shown to increase the cellular content of triacylglycerol in hepatocytes from normal and diabetic rats (44,45). We first confirmed that insulin stimulated PAI-1 synthesis in a doseand time-dependent manner.…”
Section: Discussionsupporting
confidence: 70%
“…In addition, stimulation of hepatic lipase by insulin facilitates the uptake of FFA derived from chylomicron remnants, their subsequent esterification to triglycerides and packaging into very low density lipoprotein (VLDL) particles that are exported to other tissues. [9][10][11] [12]. Importantly, apart from its stimulatory effect on glycogen formation and lipogenesis, insulin effectively blocks hepatic glycogenolysis and gluconeogenesis in the fed state [13,14].…”
Section: Introductionmentioning
confidence: 99%